2021
DOI: 10.3390/pathogens10081054
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of False-Positive Serological Results for Paratuberculosis in Mycobacterium bovis-Infected Cattle

Abstract: Both bovine tuberculosis (BTB) and paratuberculosis (paraTB) continue to cause significant economic losses in cattle breeding; in addition, their etiological agents have zoonotic potential. Although the diagnostics of both diseases are still being improved, problems still remain, such as the potential for cross-reactivity to the antigens used in tests. The aim of the present study was to confirm whether animals known to harbor Mycobacterium bovis antibodies are at increased risk of yielding positive results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…As tuberculosis has previously been confirmed in Polish zoos [ 36 , 37 ], it should be noted that MAP-positive animals can complicate the diagnosis of tuberculosis, due to cross-reactions [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As tuberculosis has previously been confirmed in Polish zoos [ 36 , 37 ], it should be noted that MAP-positive animals can complicate the diagnosis of tuberculosis, due to cross-reactions [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Monitoring the humoral immune response by bPTB-ELISA provides faster results and is a cheaper alternative to other diagnostic tools to detect infected animals. 8,10 However, different studies have questioned the usefulness of the technique due to its limited accuracy, 10,12,15,32,33 which should be considered when designing a bPTB control programme. 1,7 Different studies showed that the SE and SP values of the bPTB-ELISA ranged between 7% and 94% and 40% and 100%, respectively, 8,12 depending on the test, the sample used in the reference test (faeces or intestinal tissues), age or clinical stage of infection, 8,11 interference with other mycobacteria [14][15][16] or the time elapsed between the test and the SIT test.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Different studies showed that the SE and SP values of the bPTB-ELISA ranged between 7% and 94% and 40% and 100%, respectively, 8,12 depending on the test, the sample used in the reference test (faeces or intestinal tissues), age or clinical stage of infection, 8,11 interference with other mycobacteria [14][15][16] or the time elapsed between the test and the SIT test. 13,17,32,33 In the present study, microbiological culture of intestinal tissue (ileocaecal lymph nodes and ileocaecal valve, respectively) was used as a reference test, in contrast to most studies using faecal samples. However, tissue culture is more sensitive than faecal culture, allows detection of animals in the early stages of infection, is a postmortem technique to confirm the diagnosis of positive animals 11 and is also used to validate rapid diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the test is labor intensive and time-consuming. Consequently, many investigators have attempted to develop alternative methods [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%